Understanding Entrepreneurship Training in Incubation Hubs - Joe Kumbirai Karambakuwa; Mohamed Sayeed Bayat (CV. Literasi Indonesia, 2022)
Many scholars regard the incubation process as a mystery because little is known about what unfolds inside incubation hubs. The business incubation process is a critical initiative that can aid in the growth of new firms. However, little research has been conducted to corroborate what occurs within an incubation hub. The study was aimed at understanding what happens to start-ups in incubation hubs. The research was conducted among Harare start-up founding entrepreneurs. The case study approach was used in this qualitative study. Data was gathered using an interview guide. The sample comprised 21 start-up founders divided into three focus groups. Incubation hubs have a good impact on start-up development, according to the research. The findings offer a rare glimpse into the activities of incubation hubs. It was concluded that incubation hubs make a significant contribution that was critical to the development and survival of start-ups. The study contributed to the theoretical gap by adding more literature on start-up development.